HUBUNGAN ANTARA KOMPETENSI GURU DAN BEBAN KERJA DENGAN STRES KERJA GURU SMA NEGERI SE-KECAMATAN MANDAU KABUPATEN BENGKALIS - AKMALLUDIN AKMALLUDIN; HASNAH FAIZAH; CASKA CASKA (Universitas Riau, 2017)
This reseacrh of data consisted three variables, one dependent variable andtwo independent variables. The dependent variable (Y) is the work stress, while the firstindependent variable (X1) is teacher competence and second independent variables (X2) is theworkload. The purpose of this research was to determine the relationship of teacher competencewith work stress, workload against work stress, teacher competence and workload with workstresstogether. Respondents were teachers of State Senior High School in Mandau Sub-DistrictBengkalis Districwith totaling 160 people obtained byrandom sampling proportional technique.This research of data collected through questionnaire as a research instrument. Before thestudy tested the following instruments validity and reliability. Analysis of the data used isdescriptive analysis, statistical analysis and hypothesis testing. Based on the results of correlationcoefficient indicates a strong relationship between teacher competency against work stress of0.679 and correlation workload against occupational stress by 0.543. While jointly relationshipteacher competence and workload of the work stress of 0.757.